A Socio-Anthropological Look at Candidates Who Are Ill during the End-of-Year Exams - Silue Donakpo; Soro Nahoua Adama; Kone Siata (Richtmann Publishing, 2022)
This study addresses the issue of sick candidates during end-of-year exams. Based on qualitative socio-anthropological work in reflection on the psychology of learning, it deals with the socio-anthropological factors that weaken the psychological well-being of teachers, regardless of the discipline, during the exams. The collection tools were individual interviews and the study took place at the Peleforo GON COULIBALY University of Korhogo from April 20 to June 30, 2021. It involved a total of 64 undergraduate students selected by the reasoned method. The results show that students who do not have family support or who do not come from a family with a health or educational culture succumb to the stress of exams and fall ill. According to some respondents, these illnesses are due to an unbalanced diet, lack of physical activity and sports, and insufficient rest during the exam period. Others suffer from the negative influence of spiritual forces in their environment. Also, it appears from the investigations that the failure of the psychological well-being of learners is linked to a lack of confidence in their skills. This crisis of self-confidence causes imbalances in their being; hence the need to introduce a personal development module (which can take into account stress and fear management) in the examination programs. Received: 28 June 2022 / Accepted: 29 August 2022 / Published: 2 September 2022